Effect of Nursing Intervention Guidelines on Elderly's Knowledge Regarding Protection from Heat Wave at the Main Assiut University Hospital - Saieda Abd-Elhameed Abd-Elaziz,; Hanan Abd Allah Abozeid, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: The extreme heat can cause heat stress or heat stroke and poses dangerous effects on the brain and can end in death among elderly. Aim: To implement nursing intervention guidelines for the elderly's about protection from heat wave and evaluate its effect on elderly knowledge. Subjects and method: Quasi experimental research design was used. This study was conducted at chronic diseases outpatient clinics (diabetic clinic, internal medicine clinics, chest and cardiology clinics,) at the main Assiut University hospital. Results: Showed that (75.6%) and (78%) were illiterate and from rural areas respectively, (92.1%) of them did not know the health hazards of heat wave on elderly's health and (55%) of them did not know the measures to cool the body during heat stress before application of nursing guidelines and these percent reached zero after implementation of the nursing guidelines. Conclusion: There is improvement of the elderly's knowledge about protection from heat wave after application of nursing intervention guidelines regardless of the demographic data. Recommendation: Publication and dissemination of counseling program in all rural health units and primary health care centers to raise awareness of the elderly and their families regarding signs of heat stress, measures of protection from heat wave, health hazards of heat wave among elderly especially during summer months.